2021
DOI: 10.1177/07334648211048187
|View full text |Cite
|
Sign up to set email alerts
|

HCBS Service Spending and Nursing Home Placement for Patients With Alzheimer’s Disease and Related Dementias: Does Race Matter?

Abstract: Objectives: We examined the extent to which home and community-based services (HCBS) spending affected the likelihood of nursing home (NH) placement among black and white HCBS users with Alzheimer’s disease and related dementias (ADRD). Methods: The study population included new HCBS users with ADRD between 2010 and 2013 ( N = 1,046,200). Results: We found that a one hundred dollar increase in monthly HCBS spending was associated with a 0.3 percentage points decrease in the NH placement rate among Whites, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The variation in eligibility criteria and availability of HCBS across states has not only led to a lack of data allowing causal evaluations, but the complexity of HCBS may result in and/or exacerbate barriers to accessing services. [16][17][18][19][20] Medicaid beneficiaries face significant administrative burden and complexity that include, but are not limited to, costs to patients, eligibility requirements, availability of local service providers, and time delays. 21 These barriers contribute to and exacerbate existing disparities in access to HCBS.…”
Section: The Role Of Medicaid Home-and Community-based Services To Me...mentioning
confidence: 99%
“…The variation in eligibility criteria and availability of HCBS across states has not only led to a lack of data allowing causal evaluations, but the complexity of HCBS may result in and/or exacerbate barriers to accessing services. [16][17][18][19][20] Medicaid beneficiaries face significant administrative burden and complexity that include, but are not limited to, costs to patients, eligibility requirements, availability of local service providers, and time delays. 21 These barriers contribute to and exacerbate existing disparities in access to HCBS.…”
Section: The Role Of Medicaid Home-and Community-based Services To Me...mentioning
confidence: 99%
“…12 Higher HCBS expenditures may help older people avoid or delay any nursing home care, 13 and as a result, the expansion of HCBS spending has been linked to a population-level decline in the use of long-term care based in institutionalized settings. 9 However, the association between increased state HCBS expenditures and reduction in nursing home placement is observed for white Medicaid beneficiaries, but not for their Black counterparts, 14 suggesting that the impacts of efforts to enable aging in place may not have had an equitable impact.…”
Section: Introductionmentioning
confidence: 99%
“…Persons with dementia may be particularly at risk of experiencing preventable or unnecessary care transitions, 13 which may be further exacerbated among racial and ethnic minorities 8 . Studies have shown that ADRD is an important contributor to disparities among older adults, including impaired access to health services and poorer outcomes 14–16 . To date, however, no study has examined how PAC transitions may differentially affect minority older adults with ADRD, and the extent to which socio‐economic status, that is, dual Medicare‐Medicaid eligibility, may attenuate or exacerbate disparities in PAC outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…8 Studies have shown that ADRD is an important contributor to disparities among older adults, including impaired access to health services and poorer outcomes. [14][15][16] To date, however, no study has examined how PAC transitions may differentially affect minority older adults with ADRD, and the extent to which socio-economic status, that is, dual Medicare-Medicaid eligibility, may attenuate or exacerbate disparities in PAC outcomes. This is particularly important for older adults with dementia who are likely to experience cognitive and physical deconditioning during a hospital stay and subsequent PAC transitions to unfamiliar environments.…”
Section: Introductionmentioning
confidence: 99%